2007
DOI: 10.1016/s0968-8080(07)30315-7
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Birth Policies and Practices in Post-Reform China

Abstract: This paper comments on the provision of birthing services in Sichuan and Shanxi Provinces in China within a policy context. The goal was to understand possible unintended and harmful health outcomes for women in the light of international evidence, to better inform practice and policy development. Data were collected from October 2005 to April 2007 in 25 hospitals across 13 counties and one city. Normal and caesarean birth records were audited, observations made of facilities and interviews conducted with offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Some of these results have been published elsewhere. [27][28][29] The findings reported here drew on the same sampling base with all available women who were residents of the prefectures and had had a home birth within the previous six months and could be contacted through the MCH worker and invited to participate. We managed to interview all the eligible women (n=30) in five of the counties studied.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these results have been published elsewhere. [27][28][29] The findings reported here drew on the same sampling base with all available women who were residents of the prefectures and had had a home birth within the previous six months and could be contacted through the MCH worker and invited to participate. We managed to interview all the eligible women (n=30) in five of the counties studied.…”
Section: Methodsmentioning
confidence: 99%
“…It is increasingly common in Muhammadiyah and other private services in Indonesia to use ultrasound screening not only for early detection of multiple pregnancy and better gestational age assessment, as recommended by the World Health Organization (WHO), 20 but also to provide a visual record of the growth, formation of sexual identity and movements of the fetus. † Frequent scans have not been shown to have hazardous effects, but they are poorly justified on clinical grounds as they do not enhance perinatal outcomes.…”
Section: Trend Towards More Expensive Commercial and Unnecessary Trementioning
confidence: 99%
“…† Frequent scans have not been shown to have hazardous effects, but they are poorly justified on clinical grounds as they do not enhance perinatal outcomes. 20 Women health's organizations ask whether women are making an informed choice,** a concern raised also in other countries with a high frequency of scans, such as Syria, Viet Nam and China. [20][21][22] In a parallel trend, caesarean section is increasingly recommended in Muhammadiyah facilities as in the rest of the country and the region.…”
Section: Trend Towards More Expensive Commercial and Unnecessary Trementioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of well-established online databases was used including Medline, Maternity and Infant Care, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library Database of Systematic Reviews, Pubmed and Google Scholar. Some studies found had examined the routine policies and practices of normal birth worldwide (Maimbolwa et al, 1997;Festin et al, 2003;Turan et al, 2006;Harris et al, 2007;Danichevski et al, 2008;The SEA-ORCHID study group, 2008;Chalmers et al, 2009). In the Arab world, studies of hospital policies and practices for normal childbirth have begun to assess whether they are within EBP (Khayat and Campbell, 2000;Abdulsalam et al, 2004;Khalil et al, 2005;Wick et al, 2005;Hassan-Bitar and Wick, 2007;Sweidan et al, 2008;Khresheh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%